Some Lacunary Difference Sequence Spaces defined by Musielak-Orlicz Functions: Bipan Hazarika - Team, Support (Thai Journal of Mathematics, 2011)
In this article we are introduced the lacunary sequence spaces defined by Musielak-Orlicz functions and study their algebraic and topological properties. Also we obtain some relations related to these spaces.